Study of VO2 thin film synthesis by atomic layer deposition. (June 2019) - Prasadam, V.P.; Dey, B.; Bulou, S.; Schenk, T.; Bahlawane, N.
Abstract: Vanadium dioxide emerges as an appealing material for smart thermal management and electrical/optical switching owing to its abrupt semiconductor-to-metal transition (SMT) at near room temperature. The application potential of this material should be leveraged by the implementation of the atomic layer deposition (ALD), a method that enables an unequaled control over the thickness and film conformality on complex substrate structures by virtue of self-limiting growth mechanism. Here, the vanadium oxide thin films are synthesized from vanadyl (V) triisopropoxide (VTOP) as the vanadium precursor and H2 O as the reactant. The thermal decomposition threshold of VTOP was observed at 90 °C, and temperature window with a constant growth rate was observed at 50–90 °C. The saturation behavior of the ALD half reactions was demonstrated at 80 °C, yielding the optimized ALD cycle conditions of 8 s VTOP/15 s purge/6 s H2 O/15 s purge with a growth rate of 0.047 nm/cycle. The as-grown amorphous films convert into VO2 via a 4-h heat treatment under 10 −5  mbar at 550 °C. The formed VO2 features a sudden and reversible change in the total hemispherical reflectance in UV-VIS-NIR region at 68 °C, confirming its SMT behavior. The conversion process induces, however, a surface roughening, which was considerably suppressed by a postdeposition treatment in plasma environment prior the annealing treatment. Highlights: Vanadium oxide atomic layer deposition is performed via the thermal hydrolysis of vanadyl triisopropoxide (VTOP) at 50–90 °C. The VTOP thermolysis is revealed at and above 100 °C. Highly conformal vanadium oxide is reported on carbon nanotubes. Heat treatment at 550 °C yields VO2 with a strong semiconductor-to-metal transition behavior. Plasma and thermal treatments yield VO2 with low impact of the surface morphology.